A Strategy Model for Enhancing E-Government Procurement in UAE - Obaid, Faisal Obaid; Ali, Maimunah (Tropical Scientific Journal, 2022)
Objective: This paper presented a trategy model for enhancing E-government procurement system in UAE. Research Method: This study was administered through exploratory mode of study and collected 206 data samples through questionnaire survey. The analysis involved reliability amd multicollinearity test for validating the identified elements affecting efficiency of E-Government Procurment (E-GP) services in UAE. Findings: The analysis results revealed that the identified elements are reliable and important in affecting the efficiency of the E-GP services in UAE. Consequency, a strategy model is propsed for enhancing the efficiency of the E-GP. Originality: Development model is a new strategy model which can be implemented to enhance the efficiency of the E-service for Government procurement system of UAE.